Gamification in Project-Based Learning Using The Kahoot Application - Arifa, Rafikatul; Maulidi, Moh. Rizky; Kubro, Khodijatul; Hardiansyah, Framz (Global Action and Education for Society, 2026)
This research is motivated by the importance of innovation in learning methods to face educational challenges in the modern era. Project-based learning (PjBL) and gamification through the Kahoot application are alternatives for creating more interesting and meaningful learning. This research aims to identify the impact of gamification through Kahoot on the effectiveness of project-based learning and evaluate its effect on student motivation and learning outcomes. The method used is a systematic literature review by collecting data from various sources through searches on Google Scholar and Open Knowledge Maps using the keywords